Mechanistic target of rapamycin signaling in human nervous system development and disease - Girodengo, Marie; Ultanir, Sila K.; Bateman, Joseph M. (Frontiers in Molecular Neuroscience, 2022)
Mechanistic target of rapamycin (mTOR) is a highly conserved serine/threonine kinase that regulates fundamental cellular processes including growth control, autophagy and metabolism. mTOR has key functions in nervous system development and mis-regulation of mTOR signaling causes aberrant neurodevelopment and neurological diseases, collectively called mTORopathies. In this mini review we discuss recent studies that have deepened our understanding of the key roles of the mTOR pathway in human nervous system development and disease. Recent advances in single-cell transcriptomics have been exploited to reveal specific roles for mTOR signaling in human cortical development that may have contributed to the evolutionary divergence from our primate ancestors. Cerebral organoid technology has been utilized to show that mTOR signaling is active in and regulates outer radial glial cells (RGCs), a population of neural stem cells that distinguish the human developing cortex. mTOR signaling has a well-established role in hamartoma syndromes such as tuberous sclerosis complex (TSC) and other mTORopathies. New ultra-sensitive techniques for identification of somatic mTOR pathway mutations have shed light on the neurodevelopmental origin and phenotypic heterogeneity seen in mTORopathy patients. These emerging studies suggest that mTOR signaling may facilitate developmental processes specific to human cortical development but also, when mis-regulated, cause cortical malformations and neurological disease.